Incidental finding of cleidocranial dysplasia in an adolescent with head trauma - Sandhu, Gurpreet Singh; Lakhkar, B N; Nagrale, H R (Indian Journal of Child Health, 2014)
Cleidocranial dysplasia (CCD) is a rare autosomal dominant skeletal disease. It is characterized by partial or complete absence of clavicles, late closure of fontanels, presence of open skull sutures and multiple wormian bones and various craniofacial and dental abnormalities. The majority of craniofacial abnormalities become obvious during adolescence. Early diagnosis with preventive measures for various associated complications helps improve the quality-of-life of the patient. We hereby report an incidental finding of CCD in a 16-year-old young adolescent male with blunt head trauma and review the clinical and radiological features and associated orthopedic, dental and ENT complications of this rare disorder.